Cultural Beliefs and Traditional Practices During Pregnancy, Child Birth, and the Postpartum Period in East Gojjam Zone, Northwest Ethiopia: A Qualitative Study - Bewket Yeserah Aynalem; Misganaw Fikrie Melesse; Yibelu Bazezew Bitewa (Mary Ann Liebert, 2023)
Introduction: Many countries invest in interventions to minimize maternal and neonatal morbidity and mortality but the progress has been slow, in developing countries, especially in Africa. Traditional taboos and malpractices like home deliveries owing to cultural beliefs and traditional practices during pregnancy, childbirth, and the postpartum period increase maternal and neonatal complications. Although there are different researches in Ethiopia, the reasons for practicing such traditional activities in the East Gojjam zone in northwest Ethiopia are not well understood. Ethical clearance was obtained from the research committee of Debre Markos University. Objective: This study aimed to explore cultural beliefs and traditional practices during pregnancy, childbirth, and the postpartum period in East Gojjam Zone, Northwest Ethiopia. Materials and Methods: Purposive and snowball nonprobability sampling techniques were used to select the study participants. Data were collected through in-depth interviews and focused group discussions until the information was saturated and it was categorized and analyzed after the interviews were completed. The translated text file was analyzed using thematic analysis using codes and terms to create themes. Information from the interview consists of the women's descriptions and explanations of their cultural practices during pregnancy, childbirth, and the postnatal period. Result: Respondents report many examples of cultural, traditional, and religious practices experienced by the community in East Gojjam Zone during pregnancy, childbirth, and postpartum period, whether they are beneficial or harmful for the mother and the fetus. Drinking holy water, praying to God and Mary, taking herbal medicine, food taboo, making a confinement period in a dark room, and other cultural ceremonies are among commonly experienced cultural, traditional, and religious practices in the study area. Conclusion: Traditional, cultural, and religious practices during pregnancy, childbirth, and the postpartum period are still popular among the community in the East Gojjam Zone. It is critical to identify the harmful practices and reinforce the positive healthy practices to make pregnancy, childbirth, and postpartum periods healthy and joyful.